2010
DOI: 10.1179/016164109x12537002793968
|View full text |Cite
|
Sign up to set email alerts
|

Dokhwaljihwang-tang inhibits LPS-induced inflammatory cytokine production in peripheral blood mononuclear cells

Abstract: These results suggest the potential of Dokhwaljihwang-tang as a source of pharmaceutical acupuncture for neuronal inflammatory diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Moon showed that LPS-induced inflammatory cytokine production was inhibited by the Hyungbangjihwang-tang SY formula by blocking NF-kappa B in peripheral blood mononuclear cells (Moon et al, 2007). He also showed that the Dokhwaljihwang-tang, SY herbal formula, inhibits LPS-induced inflammatory cytokine production in peripheral blood mononuclear cells (Moon et al, 2010).…”
Section: Somatotype Characteristicsmentioning
confidence: 97%
“…Moon showed that LPS-induced inflammatory cytokine production was inhibited by the Hyungbangjihwang-tang SY formula by blocking NF-kappa B in peripheral blood mononuclear cells (Moon et al, 2007). He also showed that the Dokhwaljihwang-tang, SY herbal formula, inhibits LPS-induced inflammatory cytokine production in peripheral blood mononuclear cells (Moon et al, 2010).…”
Section: Somatotype Characteristicsmentioning
confidence: 97%